ABD AL-SHAMAD AL-PALIMBANI DAN TAREKAT SAMANIYAH DI PALEMBANG - Miftah Arifin (Al'Adalah, 2015)
As any central scientific in nusantara, a Sultanate of Palembang has produced some of the characters that play an important role in the spread of Islam in Nusantara. One of a prominent figure was Abd al-Shamad al-Palimbani. His though spend the rest of his days more in Haramyan, but His concern of the Islamic development in Nusantara is very high. He wrote the book “Siyar al-Salikin” who speak the Malay to teach it easy to understand by the Malay community. And with Tarekat Samaniyah which he brought that had a large following spread in several Nusantara areas.